Arbuscular mycorrhizal fungi on occurrence and distribution of Coleus aromaticus Benth. in Cuddalore District, Tamilnadu - P. Thamizhiniyan, M. Panneerselvam and (Journal of Ecobiotechnology, 2011)
AM fungi are vital for uptake and accumulation of iron from soil and translocation to hosts because of their high metabolic rate and strategically diffuse distribution in upper soil layers. The rhizosphere soils and root samples were collected from Coleus aromaticus Benth. fields at eight sites of cuddalore district. They were analyzed for spore number, level of arbuscular mychorrhizal (AM) colonization and AM species. The number of AM spores detected in the field soils ranged from 73 to 485 per soil. Fourteen AM species were isolated, belonging to four genera viz., Glomus, Gigaspora, Acaulospora and sclerocystis. The species composition of the AM community varied at different fields and study sites.